Objetividade jornalística: um estudo a partir da rotinas de produção das editorias de política de Zero Hora e Correio do Povo - Brixius, Leandro José (Universidade do Vale do Rio do Sinos, 2006)
This dissertation accomplishes a discussion concerning the concept of the journalistic objectivity questioned from the routines of the publications production and the politics of the Zero Hora and Correio do Povo newspapers. There to, it departures from different theoretical proposals concerning the journalistic objectivity. Following, the relationships between communication and politics are analyzed, specially the characteristics of the political covering accomplished by the news media, with special attention to the publications of politics in study. The political scenario and the political crises provoked by the denunciation of parliamentarians’ votes purchase are described by its relationship with the analyzed period. After the observed professional practices are analyzed and opposed to the journalism theories. At last some final considerations are indicated, which were concluded from the accomplished analysis
Keywords: Correio do Povo; editorial; informação; jornalismo político; objetividade; Zero Hora; Ciências Sociais Aplicadas